Preferensi Transportasi On-Line Gojek Dan Grab Dengan Metode Topsis Di Kota Pasuruan - Himmatuzzahro Himmatuzzahro; Khofifah Khofifah (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
Online transportation has become an integral part of urban mobility, providing an efficient and convenient alternative for people. This study aims to analyze user preferences between the two main online transportation platforms, namely Gojek and Grab, in the city of Pasuruan. The TOPSIS (Technique For Order of Preference by Similarity to ideal Solution) method is used to identify user preferences in the context of the city. This research was conducted through a survey of a sample of online transportation users in the city of Pasuruan. The data collected includes factors such as price, convenience, performance and security offered by Gojek and Grab. The data is then processed and normalized to obtain the relative weight of each factor based on user preferences in the city of Pasuruan. Next, positive and negative ideal matrices are formed to compare user preferences for platforms. The results of the analysis using the TOPSIS method show a user preference for Gojek of 0,56, while Grab obtains a preference value of 0,43 in the city of Pasuruan. These findings provide insight into the most influential factors in user decision making in choosing between the two platforms in the city of Pasuruan.